PENGGUNAAN MEDIA SAOSIAL DAN KEBIASAAN BELAJAR SISWA DI SMK NEGERI 1 UJUNGBATU - Tisa Oktaviani; Tri Umari; Raja Arlizon (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Data Statistics Kominfo on 2016 shows that internet usage most by individual that is for open site social media as much as 73 , 3 %. Based on the phenomenon And also several of them have been captured acces the social media where the learning process. Based on phenomenon the researchers interested for do research with the title of " Use of Social Media and Habit Learn Student ". The purpose this research are : 1) to know the using social media among students, 2) to know the learning habits from students in using social media. The type quantitative descriptive. Population in the research were are students of social media users. Sample with random sampling technique are 82 samples. And the instrument in this research is questioner with likert scale. The result from this research showing that the highest duration of social media usage is 4-5 hours everyday. The most common type social media is facebook. The highest social media usage activity is for entertainment. The result of research showed a third of students whose using social media still concentrate or focusing during lesson. Based on results research recommended to the BK teacher in order to be able guide students for wise in using social media . Next to person old expected could give supervision to her children in using social media. And to social media users are expected more utilizing social media as needs cognitive or information of a nature positive .Key Words : Social Media, Study Habit